İbn Miskeveyh’te metafizik - Özdeğirmenci, Saliha (My University, 2006)
İBN MİSKEVEYH’TE METAFİZİK İslam Felsefesi Tarihinde ve modern çalışmalarda İbn Miskeveyh’in ahlak felsefesi ön plana çıkarılmıştır. İbn Miskeveyh’in metafizik görüşlerini incelemeden ahlak felsefesinin anlaşılamayacağını düşündüğümüz için çalışmamızda filozofun metafizik görüşlerini inceledik. Felsefeyi yani hikmeti kurtuluşa götüren yol olarak gören filozof, sık sık insanın nefsini arındırması üzerinde durmakta, hakikate yaklaşabilme ve gerçek mutluluğu elde edebilme imkânını bu arınma şartına bağlamaktadır. Filozof, bu anlayışın bir sonucu olarak metafiziği daha çok ahlak ve toplumsal ilişkiler bağlamında ele almaktadır. İbn Miskeveyh’in metafiziği genel olarak “ahlak” yani doğrunun ameli hale getirilmesine teşkil edecek bir “din felsefesi” görünümündedir.

METAPHYSICS IN IBN MISQAWAIKH The Philosophy of Ethics of Ibn Misqawaikh has been treated in priority in the History of Islamic Philosophy and modern studies. As we are of the opinion that the Philosophy of Ethics of Ibn Misqawaikh cannot be comprehended without the study of his metaphysical views, we have studied the metaphysical views of the philosopher in our research. The philosopher, who deemed philosophy – i.e. Wisdom – as the pathway that leads to salvation, often weighed upon man’s purifying his carnal soul; in truth, he attributes the possibility of approaching the truth and acquiring the real happiness to this condition of purification. The Philosopher, as a consequence of this understanding, rather studied metaphysics in respect of ethics and social relationships. On the whole, the metaphysics of Ibn Misqawaikh appears to be a ‘Philosophy of Religion’ that will form the basis for the making of ‘ethics’, viz. the truth, practical.
Keywords: Felsefe_Din; İslam Dini_Metafizik